PERILAKU BERKENDARA PADA SISWA SMA NEGERI 1 RENGAT - Putri, Monifa; Syamlingga Putri, Anjeli Ratih (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2021)
Traffic accidents are a health problem that needs attention, because the impact caused by traffic accidents is material loss, disability, and even death. Based on data on traffic accidents at the Indragiri Hulu Police in 2019, the second most professional traffic accident perpetrator is 23 students after private employees, namely 69 people. In addition, based on the types of motorized vehicles involved in traffic accidents, the majority of motorbikes were 168 units. As many as 58.34% of students at SMA Negeri 1 Rengat use motorbikes to school. Therefore, it is necessary to know how the driving behavior of students of SMA Negeri 1 Rengat. The research method used is qualitative (exploratory study). The selected informants were 56 people with purposive sampling method. The data was collected by means of focus group discussions, in-depth interviews, document study and observation. The results of interviews with several informants showed that traffic accidents in adolescents were caused by the disorderly behavior of adolescents. The need for increased information and education about traffic accidents for high school students by the police and related parties